High-Performance Ultra-Compact Dual-Band Bandpass Filter for Global System for Mobile Communication-850/Global System for Mobile Communication-1900 Applications - Rezaei, Abbas; Yahya, Salah I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
This work presents a novel microstrip dual-band bandpass filter (BPF) using meandros spirals and patch cells, which is proposed for the first time by this work. It occupies a very compact size of 0.0017 λg2. The proposed filter is designed to operate at Fo1=0.85 GHz and Fo2=1.85 GHz for GSM-850/GSM-1900 applications. In addition to the small size, it has several advantages in terms of wide fractional bandwidths (FBW), low insertion losses and high return losses at both channels. The simulated insertion losses at the lower and upper passbands are 0.05 dB and 0.1 dB, respectively. Another advantage of the proposed BPF of this work is the attenuated harmonics, where it is able to suppress 1st, 2nd, 3rd and 4th harmonics (4.11 Fo1) with -20 dB maximum harmonic level.